PENGARUH LEVEL ZINK DALAM PENGENCER TRIS KUNING TELUR TERHADAP KUALITAS SEMEN CAIR SAPI ANGUS (The effect of zinc level in the tris egg yolk extender on the quality of angus liquid semen) - Siena, Sofia M.S.; Hine, Thomas Mata; Nalley, W. Marlene; Marawali, Aloysius (JURNAL NUKLEUS PETERNAKAN, 2024)
Efforts to improve cattle productivity can be done by using artificial insemination (AI) technology. Many factors determine the success of AI, one of which is the diluent used in semen preservation. The purpose of this study was to determine.the effect.of zinc level in.tris-egg yolk.diluent (T-EY) on the.quality of liquid semen of Angus bull. Semen is collected once a week using.an artificial.vaginal method from a three-year-old Angus bull in an undisturbed or healthy body and reproductive organs. Semen was diluted with T-EY diluent which had been added with zinc at several levels, 0 mg control treatment (T0), 10.mg (T1), 20.mg (T2), 30.mg (T3), 40 mg (T4). The diluted semen was.stored at a temperature of 3-5oC, then observed every 24 hours for.motility, viability,.abnormalities and survival of.spermatozoa to a minimum motility of 40%. The.results showed.that the addition of 20 mg of zinc in the T-EY.diluent (T2) resulted in a higher.quality of liquid semen of Angus bull (P˂0.05) than other.treatments. The quality of the liquid semen (motility, viability, abnormalities and survival of spermatozoa) were motility 44±5.75%, viability 48.39±13.59%, abnormality 6.91±1.85% and durability.live 5.60±0.89 days. It was.concluded that the.addition.of 20 mg zinc in the.tris-egg yolk diluent produced liquid semen of Angus bull with higher quality than other treatments.